Fixed-Point Theorem for Multivalued Quasi-Contraction Maps in a V-Fuzzy Metric Space - Matthew Brijesh Sookoo; Sreedhara Rao Gunakala (Abstract and Applied Analysis, 2020)
In this paper, we introduce the concept of a set-valued or multivalued quasi-contraction mapping in V-fuzzy metric spaces. Using this new concept, a fixed-point theorem is established. We also provide an example verifying and illustrating the fixed-point theorem in action.